2010
DOI: 10.1007/s10461-010-9836-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Addressing Depression in HIV Research: Assessment, Cultural Context, and Methods

Abstract: Depression is one of the most common co-morbidities of HIV infection. It negatively impacts self-care, quality of life, and biomedical outcomes among people living with HIV (PLWH) and may interfere with their ability to benefit from health promotion interventions. State-of-the-science research among PLWH, therefore, must address depression. To guide researchers, we describe the main diagnostic, screening, and symptom-rating measures of depression, offering suggestions for selecting the most appropriate instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
122
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 122 publications
6
122
1
Order By: Relevance
“…44 Depression screening should be offered universally to newly diagnosed MSM and depression treatment should be provided, when applicable. Integrating treatment for depression into HIV care, including cognitive behavioral therapy (CBT) and pharmacological approaches, has been successful among patients living with HIV 45 and, in turn, can increase HIV treatment adherence. 46 So that both partners in a sexual relationship can make informed decisions about risk reduction, 47 efforts to increase disclosure should specifically address disclosure self-efficacy for the different types of partners and situations in which one may need to disclose.…”
Section: Discussionmentioning
confidence: 99%
“…44 Depression screening should be offered universally to newly diagnosed MSM and depression treatment should be provided, when applicable. Integrating treatment for depression into HIV care, including cognitive behavioral therapy (CBT) and pharmacological approaches, has been successful among patients living with HIV 45 and, in turn, can increase HIV treatment adherence. 46 So that both partners in a sexual relationship can make informed decisions about risk reduction, 47 efforts to increase disclosure should specifically address disclosure self-efficacy for the different types of partners and situations in which one may need to disclose.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is one of the most common comorbidities of HIV infection (Simoni et al, 2011). Previous studies have shown that depression not only negatively impacts the QoL of PLWHA (Briongos Figuero, Bachiller Luque, Palacios Martin, Gonzalez Sagrado, & Eiros Bouza, 2011;Simoni et al, 2011) but also relates to rapid disease progression (Gore-Felton et al, 2006), as evidenced by a decline in CD4+ cell count, increased viral load, higher frequencies of health care visits and hospitalizations, and reduced survival rates (Mavandadi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that depression not only negatively impacts the QoL of PLWHA (Briongos Figuero, Bachiller Luque, Palacios Martin, Gonzalez Sagrado, & Eiros Bouza, 2011;Simoni et al, 2011) but also relates to rapid disease progression (Gore-Felton et al, 2006), as evidenced by a decline in CD4+ cell count, increased viral load, higher frequencies of health care visits and hospitalizations, and reduced survival rates (Mavandadi et al, 2009). Depression is associated with worsening disease management because depressive symptoms may have a negative effect on medication adherence and compliance with treatment regimens (Mavandadi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been linked with poor medication adherence among individuals infected with HIV, 4 and even depressive symptoms that do not meet diagnostic criteria for major depressive disorder can disrupt self-care behaviors such as poor adherence to HIV treatment regimens. 5 Adherence to combined antiretroviral therapy (cART) regimens is important in managing HIV infection and improving health by lowering viral load, improving CD4 T cell counts, and decreasing susceptibility to opportunistic diseases. 6,7 However, cART adherence is only one part of a larger picture of health maintenance in HIV/AIDS.…”
mentioning
confidence: 99%